Langmuir waves excitation by electron beam with the limited cross-section in the near-Eearth electron foreshock - Anisimov, I.O.; Krasnosselskikh, V.V.; Musatenko, K.S. (Вопросы атомной науки и техники, 2005)
Model of the stripped monoenergetic electron beam with the sharp boundaries based on the results of CLUSTER measurements is proposed for the near-Earth foreshock vicinity. Dispersion equation is obtained and analyzed using numerical methods. Dependency of the equation roots corresponding to kinetic mechanism of beam-plasma instability on the model parameters is studied. Запропоновано модель моноенергетичного стрічкоподібного пучка з різкими границями, яка базується на результатах вимірювань експерименту КЛАСТЕР в області форшоку ударної хвилі Землі. Було отримано дисперсійне співвідношення, яке проаналізовано числовими методами. Вивчені залежності положення коренів, що відповідають кінетичному механізму плазмово-пучкової нестійкості, від параметрів моделі. Предложена модель моноэнергетического ленточного пучка с резкими границами, которая базируется на результатах измерений эксперимента КЛАСТЕР в области форшока ударной волны Земли. Было получено дисперсионное уравнение и проанализировано числовыми методами. Изучены зависимости положения корней дисперсионного уравнения, соответствующих кинетическому механизму плазменно-пучковой неустойчивости, от параметров модели.